The Relation between Nutritional Status and Acne in Female Teenagers Ages 15-17 years old in Surakarta - Chithivema, Egtheastraqita; Widardo, .; Riyadi, Slamet (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Acne is one of the most common skin problems especially on teenagers. Acne is resulted from chronic inflammation on sebaceous gland. Acne can be caused by some factors, one of them is the increase of sebaceous gland production which can be caused by over nutrition / obesity. This research aims to see the relation between nutritional status and acne on female teenagers age 15 â 17 years old in Surakarta. Methods: This is an observational analytic research with cross sectional approach. The research was done in 5 high schools in Surakarta, which are SMA Negeri 1, SMA Negeri 7, SMA Muhammadiyah 3, SMA Batik 1, and SMA Islam Diponegoro. Sample used are 15 â 17 years old female student, not on menstruation / 1 week before menstruation period, have not use cosmetics for the past 1 week, not on acne treatment, and not on antibiotic or steroid. The sampling method used was purposive random sampling after inclusive and exclusive selection based on research criteria. Dependent variable is acne, and independent variable is nutritional status. Research subject completed (1) informed consent, (2) acne questionnaire, (3) bio data and food recall questionnaire, (4) height and weight measurement. As much as 196 data were collected and analyzed using Chi-Squared followed by Odds Ratio (OR) finding. Result: Result shown p = 0,001 (p < 0,05) from data analysis with significance number Î± = 0,05 and OR value = 6,923. Conclusion: Statistically, there is a significant relation between nutrition status and acne on female teenagers age 15 â 17 years old in Surakarta. Keywords: acne, nutritional statusÂ